Novel Plant-Based Metabolites as Disinfectants against Acanthamoeba castellanii - Ruqaiyyah Siddiqui; Noor Akbar; Bushra Khatoon; Muhammad Kawish; Muhammad Shaiq Ali; Muhammad Raza Shah; Naveed Ahmed Khan (MDPI AG, 2022)
Due to global warming, coupled with global water shortages and the reliance of the public on household water tanks, especially in developing countries, it is anticipated that infections caused by free-living amoebae such as Acanthamoeba will rise. Thus, the development of novel disinfectant(s) which can target pathogenic free-living amoebae effectively is warranted. Herein, we extracted and isolated several plant-based secondary metabolites as novel disinfectants for use against pathogenic Acanthamoeba. The identity of the compounds was confirmed by nuclear magnetic resonance and tested for antiamoebic activities against clinical isolate of A. castellanii, belonging to the T4 genotype. Amoebicidal assays revealed that the compounds tested showed antiamoebic properties. Betulinic acid and betulin exhibited parasite killing of more than 65%. When tested against the cyst stage, betulinic acid, betulin, and vanillic acid inhibited both encystation and excystation processes. Furthermore, the plant-based metabolites significantly inhibited the binding capability of A. castellanii to host cells. Finally, most of the tested compounds displayed minimal cytotoxic activities against human cells and noticeably perturbed amoeba-mediated host cell cytotoxicity. Notably, both alkaloid and betulinic acid showed 20% cytotoxic effects, whereas betulin and lupeol had cytotoxic effects of 24% and 30%, respectively. Overall, our findings indicate that plant-based natural compounds demonstrate anti-Acanthamoebic properties, and they have potential candidates for water disinfectants or contact lens disinfecting solutions, as well as possible therapeutic drugs against Acanthamoeba infections.